IL‐37 inhibits invasion and metastasis in non‐small cell lung cancer by suppressing the IL‐6/STAT3 signaling pathway. Issue 5 (25th March 2018) - Jiang, Mingfang; Wang, Ye; Zhang, Hua; Ji, Youxin; Zhao, Peng; Sun, Rongli; Zhang, Chunling
Abstract : Background: IL‐37 has been identified as a fundamental inhibitor of inflammatory and immunity responses. It plays a crucial protective role in several cancers, but its anti‐tumor activity and the potential regulatory mechanism of IL‐37 in non‐small cell lung cancer (NSCLC) is largely unclear. Methods: Enzyme‐linked immunosorbent assay was used to detect plasma IL‐37 expression in NSCLC patients and healthy controls. The NSCLC cell line A549 was cultured with recombinant human IL‐37 or recombinant human IL‐6 protein. A549 invasion and metastasis were detected using Transwell invasion and scratch wound healing assays, respectively. Protein expression of STAT3, pSTAT3, E‐cadherin, vimentin, and N‐cadherin were detected using Western blotting, and messenger RNA expression of STAT3, E‐cadherin, vimentin, and N‐cadherin was assessed in each group using real time PCR. Results: IL‐37 plasma expression was decreased in NSCLC patients, and the downregulation of IL‐37 was correlated with tumor stage. In vitro, IL‐37 inhibited invasion and migration in A549 cells, while IL‐6 promoted invasion and migration in A549 cells. pSTAT3, vimentin, and N‐cadherin expression was increased. E‐cadherin expression was lower in the IL‐6 group than in the control group; however, the opposite pattern was observed in the IL‐37 + IL‐6 group. Conclusion: Our results showed that IL‐37 plays an inhibitory role in NSCLC progression, possibly by suppressing STAT3 activation and decreasing epithelial‐to‐mesenchymal transition by inhibiting IL‐6 expression. IL‐37 could serve as a potential novel tumor suppressor in NSCLC.